Transformasi Media dan Budaya Baru : Ketidakpatuhan Lalu Lintas Pengendara terhadap Penerapan ETLE (E-Tilang) di Kota Bengkulu - Sijabat, Putra Michael; Nopianti, Heni; Hanum, Sri Handayani (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2024)
Abstract: This article describes the research findings behind the implementation of ETLE in motorists’ understanding and the causes of motorists' non-compliance with the implementation of CCTV-based ETLE (Electronic Traffic Law Enforcement) in Bengkulu City. The qualitative method uses non-participant observation techniques, interviews, triangulation and secondary data in the data collection process. Informants were determined by purposive sampling. The research data were analyzed using Robert K. Merton's functional structural theory. The results showed that the application of ETLE in the understanding of motorists in Bengkulu city is that this system is less effective. They argue that ETLE tends to be a form of excessive surveillance that is inappropriate in law enforcement. Motorists are also concerned about potential technical errors in the system that could result in unfairness or confusion in the administrative process. Meanwhile, the causes of motorist non-compliance with ETLE (Electronic Traffic Law Enforcement) in Bengkulu City are the low understanding of motorists towards ETLE and the culture of neglect of motorists in ignoring this ETLE system. The importance of awareness and knowledge of the use of CCTV-based ETLE (Electronic Traffic Law Enforcement) for motorists is the main focus of this topic. In addition, policymakers and law enforcement officials can take strategic steps to increase the use of CCTV-based ETLE.